PENYULUHAN DAN SOSIALISASI POLA HIDUP HEMAT ENERGI LISTRIK - Syukri Syukri; Muliadi Muliadi; T. Murisal Asyadi; Cut Daili; Bukhari Bukhari (Universitas Pahlawan Tuanku Tambusai, 2022)
The development of increasingly modern technology, the role of electricity in life is very important for both society and the industrial world 4.0. Seeing the condition of the people who still do not have awareness in how to save electricity use, it is necessary to have counseling and socialization that can add insight to the community so that they can know more about the use of electric energy on a daily basis. Therefore it is carried out with the Counseling method and socialization of energy-saving lifestyles that can equip people in the use of electricity in everyday life so that from this activity the community understands more about electricity and provides awareness to change patterns of electricity consumption by saving energy and using electronics low power. With this counseling method, it is found that the community understands more and impacts awareness about the use of electrical energy more wisely and gains new insights regarding patterns of electrical energy use in everyday life by saving energy so as to provide benefits for the community itself. Keywords: Counseling, Energy Save, Electrical